Hit by the Silk Road: How Wage Coordination in Europe Mitigates the China Shock - Erling Barth; Henning Finseraas; Anders Kjelsrud; Karl Ove Moene (Institute of Labor Economics (IZA), 2020)
Coordination in collective wage setting can constrain potential monopoly gains to unions in non-traded-goods industries. Countries with national wage coordination can thus stabilize overall employment against fluctuations and shocks in the world economy. We test this theory by exploring within-country variation in exposure to competition from China in 13 European countries. Our causal estimates demonstrate that in countries with uncoordinated wage setting, regions with higher import exposure from China experienced a marked fall in employment, while countries with wage-coordination experienced no such employment effects. We test our main mechanism against other explanations, and show that our findings are robust to alternative measures of wage coordination, industry classifications, and trade exposure.
Keywords: F16; F66; J51; J60; 330; wage-coordination; employment; globalization; China-shock